Microglial NF-κB drives tau spreading and toxicity in a mouse model of tauopathy - Chao Wang; Li Fan; Rabia R. Khawaja; Bangyan Liu; Lihong Zhan; Lay Kodama; Marcus Chin; Yaqiao Li; David Le; Yungui Zhou; Carlo Condello; Lea T. Grinberg; et al. (Nature Communications, 2022)
Wang et al show that microglial NF-κB activation is essential for tau spreading and tau-mediated spatial learning and memory deficits in tauopathy mice. Inactivation of NF-κB reversed tau associated microglial states and rescued autophagy deficits.